Validation of Cyber Test for Future Soldiers: A Test Battery for the Selection of Cyber Soldiers - Lif, Patrik; Sommestad, Teodor; Albinsson, Pär-Anders; Valassi, Christian; Eidenskog, Daniel (Frontiers in Psychology, 2022)
To facilitate recruitment of conscript cyber soldiers in Sweden, the Cyber Test Future Soldiers (CTFS) was developed as a complement to the existing generic enrolment test (I-prov 2000). Consisting of several parts, CTFS measures different aspects of computer-related knowledge and cognitive abilities that we believe are of particular relevance to cyber security. This article describes the evaluation regarding CTFS’s validity and reliability based on data from 62 conscripts that took the test and the 27 selected conscripts finishing the training one year later (being the first to do so). Reliability was predicted through internal consistency and test-retest measures. Cronbach’s alpha for CTFS ranges from 0.79 to 0.86 whereas the test-retest reliability is 0.60. Evidence regarding validity was collected based on test content and internal structure. Convergent, discriminant and predictive evidence are also presented. Perhaps most importantly, CTFS could predict the cyber soldiers’ performance during their training, and added incremental validity to I-prov 2000. When adjusted for range restriction, I prov 2000 predicted 20% of the variation in course score, while 34% of the variance was explained when CTFS was used in conjunction with I-prov 2000. The results show that CTFS already in its first version is adding value for the Swedish Armed Forces.